Desain Dan Penentuan Lokasi Pembebanan Pendulum Alat Uji Impak Untuk Pengujian Produk Hasil Las Gesek Rotary Bar-Plate - Panji Adino; Yohanes Yohanes; Muftil Badri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fracture that occurred in bar-plate friction welding joint on component, be it with a similar or dissimilar materials, can be reviewed by destructive testing. One of the destructive test on weld joint by friction welding is the impact test. Pendulum of standart Charpy and Izod is not match to use for it. Therefore, in this study was made the design and set up pendulum of impact testing for it, using the finite element method software, by considering dynamic factors that may affect fracture such as, loading angle, loading point on the product bar-plate, the dimensions of pendulum, maximum stess thet occurs, and the mass variation of the pendulum. The Obtain summaries are as follows: (1) Results of the Pendulum tests, it was safe to use, it was qualyfied for pendulum impact testing, and plastic deformation was not occurs on entire pendulum. (2) Based on tests result, loading point (x) at 10mm, affected fracture between bar and plate in HAZ section, while loading point at 40 mm until 15 mm affected fracture on plate, not on the section between bar and plate.Keywords: Bar-plate friction welding, Loading point.